Study on Effect of Tandem Charges with Different Charge Mass Ratios on Underwater Explosion Power - Wei ZHANG; Rui GUO; Hao CUI (水下无人系统学报, 2025)
In order to explore the influence of different charge mass ratios of tandem charges on the underwater explosion power, theoretical analysis of the impulse of the underwater explosion shock wave induced by tandem charges was carried out according to the empirical formula of the underwater shock wave, and the underwater explosion power of tandem charges with different charge mass ratios was numerically simulated. Under the same charge mass, the underwater explosion output impulse laws and the damage effects on the target structure of the tandem charge with different charge mass ratios and single charge were compared. At the same time, a scaled-down water tank test on the damage to the target structure caused by the tandem charge was carried out. The results show that when the total charge is 400 g TNT, the underwater explosion output impulse of the tandem charge structure and its effect on the target panel are obviously better than that of a single charge, and the explosion power of the tandem charge increases with the increase in the charge ratio η. When η is 1:1, the impulse gain and the deflection of the target panel are the largest, and the impulse gain is increased by 27.43%; the deflection of the target panel is increased by 23.58%. The scaled-down experiment results of small charges show good agreement with the theoretical analysis and numerical simulation results.